Sex Variations in Retinal Microcirculation Response to Lower Body Negative Pressure - Adam Saloň; Nikola Vladic; Karin Schmid-Zalaudek; Bianca Steuber; Anna Hawliczek; Janez Urevc; Andrej Bergauer; Vid Pivec; Vishwajeet Shankhwar; Nandu Goswami (Biology, 2023)
Introduction: Lower body negative pressure (LBNP) is routinely used to induce central hypovolemia. LBNP leads to a shift in blood to the lower extremities. While the effects of LBNP on physiological responses and large arteries have been widely reported, there is almost no literature regarding how these cephalad fluid shifts affect the microvasculature. The present study evaluated the changes in retinal microcirculation parameters induced by LBNP in both males and females. Methodology: Forty-four participants were recruited for the present study. The retinal measurements were performed at six time points during the LBNP protocol. To prevent the development of cardiovascular collapse (syncope) in the healthy participants, graded LBNP until a maximum of −40 mmHg was applied. A non-mydriatic, hand-held Optomed Aurora retinal camera was used to capture the retinal images. MONA Reva software (version 2.1.1) was used to analyze the central retinal arterial and venous diameter changes during the LBNP application. Repeated measures ANOVAs, including sex as the between-subjects factor and the grade of the LBNP as the within-subjects factor, were performed. Results: No significant changes in retinal microcirculation were observed between the evaluated time points or across the sexes. Conclusions: Graded LBNP application did not lead to changes in the retinal microvasculature across the sexes. The present study is the first in the given area that attempted to capture the changes in retinal microcirculation caused by central hypovolemia during LBNP. However, further research is needed with higher LBNP levels, including those that can induce pre-fainting (presyncope), to fully understand how retinal microcirculation adapts during complete cardiovascular collapse (e.g., during hypovolemic shock) and/or during severe hemorrhage.